Class I major histocompatibility complex-restricted cytolytic T lymphocytes recognize a limited number of sites on the influenza hemagglutinin. - Braciale, T J (1989)
Two distinct regions of the influenza A/JAP/305/57 hemagglutinin molecule are identifiable as sites recognized by murine class I major histocompatibility complex (MHC) (H-2d)-restricted cytolytic T lymphocytes (CTL) generated in response to immunization with infectious type A influenza virus. Each of these sites can be mimicked by a synthetic oligopeptide of approximately 20 amino acids. Data presented herein indicate that these two sites define the dominant immunogenic epitopes on the hemagglutinin recognized by H-2Kd-restricted CTL. These same sites are not efficiently recognized by hemagglutinin-specific class I MHC-restricted CTL of several unrelated MHC haplotypes. These observations show that even for a large complex glycoprotein molecule like the influenza hemagglutinin, only a limited number of class I CTL recognition sites are generated in the infected cell and that the subset of immunogenic epitopes is dependent on the MHC haplotype of the responding individual. These parameters need to be considered in the design of synthetic and recombinant vaccines.